Identification of the Nuclear Localization Signal in Xenopus Cyclin E and Analysis of Its Role in Replication and Mitosis - Moore, Jonathan D. (The American Society for Cell Biology, 2002)
Cyclin-dependent kinase (Cdk)2/cyclin E is imported into nuclei assembled in Xenopus egg extracts by a pathway that requires importin-α and -β. Here, we identify a basic nuclear localization sequence (NLS) in the N-terminus of Xenopus cyclin E. Mutation of the NLS eliminated nuclear accumulation of both cyclin E and Cdk2, and such versions of cyclin E were unable to trigger DNA replication. Addition of a heterologous NLS from SV40 large T antigen restored both nuclear targeting of Cdk2/cyclin E and DNA replication. We present evidence indicating that Cdk2/cyclin E complexes must become highly concentrated within nuclei to support replication and find that cyclin A can trigger replication at much lower intranuclear concentrations. We confirmed that depletion of endogenous cyclin E increases the concentration of cyclin B necessary to promote entry into mitosis. In contrast to its inability to promote DNA replication, cyclin E lacking its NLS was able to cooperate with cyclin B in promoting mitotic entry.